2020
DOI: 10.26719/2020.26.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and underweight in schoolchildren in Constantine, Algeria: comparison of four reference cut-off points for body mass index

Abstract: Background: Algeria is experiencing a nutritional transition and increasing overweight in children. Aims: This study aimed to determine the prevalence of overweight and underweight in children aged 6-10 years in Constantine city, Algeria using four international reference cutoffs for body mass index. Methods: A cross-sectional study was conducted between February and May 2015 with a sample of 509 schoolchildren aged 6-10 years. Height and weight were measured according to World Health Organization (WHO) recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…The same trend was also observed among both boys (6.9% vs. 4.5% and 4.5% for overweight and 2.2% vs. 2.0% and 1.0% for obesity, respectively) and girls (7.9% vs. 5.2% and 5.8% for overweight and 2.2% vs. 2.3% and 1.4% for obesity, respectively). These findings were consistent with the earlier studies with the Algerian [25], Malaysian [26] and Saudi [27] child samples. A study in Lahore, Pakistan, found that 1860 schoolchildren had a higher prevalence of overweight and obesity when measured against the WHO reference compared to the IOTF and CDC references [28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The same trend was also observed among both boys (6.9% vs. 4.5% and 4.5% for overweight and 2.2% vs. 2.0% and 1.0% for obesity, respectively) and girls (7.9% vs. 5.2% and 5.8% for overweight and 2.2% vs. 2.3% and 1.4% for obesity, respectively). These findings were consistent with the earlier studies with the Algerian [25], Malaysian [26] and Saudi [27] child samples. A study in Lahore, Pakistan, found that 1860 schoolchildren had a higher prevalence of overweight and obesity when measured against the WHO reference compared to the IOTF and CDC references [28].…”
Section: Discussionsupporting
confidence: 93%
“…The agreement was moderate to excellent (κ ≥ 0.8) when examining child obesity, particularly between the WHO and CDC references. These results were also consistent with the Algerian and Malaysian study results [25,26] revealing that the agreement was excellent between the WHO and CDC for examining childhood obesity. In contrast, a comparison between three international references and the population's own BMI reference showed a poor agreement (i.e., κ < 0.6), which is also parallel to earlier research results [24].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, while no official assessment of food advertisements has been conducted in Tunisia, similar countries from the Eastern and Mediterranean regions are frequently exposed to unhealthy food advertisements in mass media [ 43 ]. The anthropometric parameters trends in Tunisia are similar to those reported in proximal North African countries (e.g., Algeria and Morocco) which showed a rising of the excess of adiposity [ 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 80%
“…In Algeria, few studies have been published on overweight in early childhood (less than five years) 13,14 . However, several studies on children and adolescents in school at the age of 4 to12 years old have been published at several regional levels; for example in Constantine in 2009, 2014 and 2020, the prevalence of overweight and obesity in children was equal to 23.10 % from 6 to 12 years old 15 , and 8.5 % (overweight) and 19.3 % (obese) from 10 to 11 years old, and 22.8 to 28.3 % from 6 to10 years 16 , respectively. In Tebessa, in 2007 and 2010, the prevalence was 17.39 % from 4 to 13 years old and 6.36 % from 5 to 8 years old 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…was recorded in16.67 % of normal-weight children and 91.67 % of overweight and obese children. The reasons that explain this practice are that the children watch television while swallowing large quantities.…”
mentioning
confidence: 99%